PENGARUH KARAKTERISTIK PERUSAHAAN DAN CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT PADA PERUSAHAAN LQ45 YANG TERDAFTAR - Azwir Nasir; Elfi Ilham; Vadela Irna Utara (Jurnal Ekonomi, 2014)
This study aimed to determine the effect of companies characteristics andcorporate governance consisting of profitability, liquidity, leverage, activityanalyze, size, audit committee, board of directors and governancecommitteetowards sustainability report publication in LQ45 companies listed inIndonesian Stock Exchange in 2008-2011.The data used in this study are secondary data from financial data in theIndonesian Stock Exchange. The sample method used was purposive sampling, ofthe population of 45 companies listed in the Indonesian Stock Exchange, researchsample counted 11 companies that meet the criteria. Hypothesis testing is done byusing logistic regression analysis.The results of this research base on hypothesis test indicates that liquidity, activityanalyze, size, audit committee and board of directors has no significant effect tosustainability report publication with significant are 0.052, 0.213, 0.084, 0.564dan 0.111, while the profitability, leverage and governance committee hassignificant influence to sustainability report publication with significant is 0.008,0.022 dan 0.043. The magnitude of the effect (Nagelkerke R-Square) of thefinancial reporting quality, institutional ownership and firm size on asymmetry ofinformation was 77,6%. While the remaining 22,4% is influenced by othervariables.Keywords :Sustainability Report, Return on Assets, Current Ratio, Debt ToEquity, Inventory Turnover, Size, Audit Committee, Board ofDirectors, and Governance Committee.